An Experimental Analysis on Dispatching Rules for the Train Platforming Problem in Busy Complex Passenger Stations - Zeng, Qiongfang; Zhang, Yinggui; Lei, Dingyou (Promet - Traffic&Transportation, 2017)
This paper presents the scheduling models for train platforming problem (TPP) by using mixed integer linear programming and job shop scheduling theory. First, the operation procedures and scheduled time adjustment costs of different train types specific to busy complex passenger stations are explicitly represented. Second, a multi-criteria scheduling model (MCS) for TPP without earliness and tardiness time window (ETTW) and a time window scheduling model (TWS) with ETTW for TPP are proposed. Third, various dispatching rules were designed by incorporating the dispatcher experiences with modern scheduling theory and a rule-based metaheuristic to solve the above model is presented. With solution improvement strategies analogous to those used in practice by dispatchers, the realistic size problems in acceptable time can be solved.